If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 32 + -3x = -10 Solving 32 + -3x = -10 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-32' to each side of the equation. 32 + -32 + -3x = -10 + -32 Combine like terms: 32 + -32 = 0 0 + -3x = -10 + -32 -3x = -10 + -32 Combine like terms: -10 + -32 = -42 -3x = -42 Divide each side by '-3'. x = 14 Simplifying x = 14
| -3*[5*(9-2)-2*3]= | | 4r^4+15r^2=4 | | 2s^2+15s-4=0 | | 0.2586= | | R-12=21 | | 0.1498= | | -5(-7)= | | -20.3+1= | | 7c=490 | | 2x^3-x^2y+9x^2+y^2-5xy+7x-2y-3=0 | | 4x[3(3-2)-8]= | | 2x^2-3x-18=0 | | 9x+8+4x=7x+16 | | 5.0x^2-10.0x-7.0=0 | | 8+(-11)= | | 8-11= | | 2p^2-12p+17=0 | | 5-2(a+1)=9+a | | U^2+3U-10=0 | | 3(-6)= | | 48-(-10)= | | 2x^2-18x-36=0 | | -21/(-3)= | | x^2+10x+25=31 | | -8-(-9)+(-3)= | | (2x-20)+(x+8)= | | 15x-7=8+12x | | 4+(-4)= | | 3p^2+3p-7=0 | | x^2+18x=4 | | 5(x+3)+4x-3=-(2x-4)+2 | | 3.5+0.25-1.00= |